Toxic Bradycardias in the Critically Ill Poisoned Patient - Melissa L. Givens (Emergency Medicine International)
Cardiovascular drugs are a common cause of poisoning, and toxic bradycardias can be refractory to standard ACLS protocols. It is important to consider appropriate antidotes and adjunctive therapies in the care of the poisoned patient in order to maximize outcomes. While rigorous studies are lacking in regards to treatment of toxic bradycardias, there are small studies and case reports to help guide clinicians’ choices in caring for the poisoned patient. Antidotes, pressor support, and extracorporeal therapy are some of the treatment options for the care of these patients. It is important to make informed therapeutic decisions with an understanding of the available evidence, and consultation with a toxicologist and/or regional Poison Control Center should be considered early in the course of treatment.